2000
DOI: 10.1094/pdis.2000.84.8.885
|View full text |Cite
|
Sign up to set email alerts
|

New Source of Resistance to Cucumber mosaic virus in Capsicum frutescens

Abstract: A small-fruited pungent pepper accession, Capsicum frutescens ‘BG2814-6’, is resistant to several isolates of Cucumber mosaic virus (CMV). Resistance in BG2814-6 is incompletely penetrant and is controlled by at least two major recessive genes. The accession BG2814-6 and C. annuum ‘Perennial’, the leading source of CMV tolerance, appear to share one or more CMV resistance genes. CMV was detected in uninoculated leaves in a small percentage of both BG2814-6 and Perennial plants, indicating that resistance is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…1, Cooley et al, 2000; 2, Ren et al, 2000; 3, Takahashi et al, 2001; 4, Takahashi et al, 2002; 5, Takahashi et al, 2004; 6, Sekine et al, 2006; 7, Chisholm et al, 2000; 8, Whitham et al, 2000; 9, Decroocq et al, 2009; 17, Provvidenti and Hampton, 1992; 18, Ma et al, 2010; 25, Moury and Verdin, 2012; 30, Grube et al, 2000; 31, Tomita et al, 2008; 32, Tomita et al, 2011; 33, Matsumoto et al, 2008; 34, Sawada et al, 2004; 43, De La Cruz et al, 1997; 44, Holmes, 1937; 45, Berzal-Herranz et al, 1995; 50, Anagnostou et al, 2000; 65, Hayes et al, 2004; 66, Hajimorad and Hill, 2001; 67, Hajimorad et al, 2005a; 68, Wen et al, 2013; 69, Eggenberger et al, 2008; 105, Whitham et al, 1994; 106, Erickson et al, 1999; 107, Baker et al, 1995; 108, Dinesh-Kumar et al, 1995; 109, Dinesh-Kumar et al, 2000; 110, Padgett and Beachy, 1993; 111, Padgett et al, 1997; 127, Vallejos et al, 2006; 128, Ariyarathne et al, 1999; 129, Collmer et al, 2000; 130, Kelly et al, 1995; 131, Kyle et al, 1986; 132, Fisher and Kyle, 1994; 133, Fisher and Kyle, 1996; 134, Zhou et al, 2007; 135, Garrido-Ramirez et al, 2000; 136, Seo et al, 2004; 137, Seo et al, 2007; 138, Wang et al, 1999; 139, Gururani et al, 2012; 156, Seo et al, 2006; 158, Yang et al, 2003; 159, Rai, 2006; 160, Harper et al, 2010; 166, Hanson et al, 2000; 167, Verlaan et al, 2013; 169, Ishibashi et al, 2007; 170, Ishibashi et al, 2012; 171, Pelham, 1966; 172, Yamafuji et al, 1991; 173, Meshi et al, 1988; 174, Kato et al, 2013; 179, Finlay, 1953; 180, Holmes, 1948; 181, Brommonschenkel et al, 2000; 182, Hallwass et al, 2014; 183, Hoffmann et al, 2001; 188, Hall, 1980; 189, Meshi et al, 1989…”
Section: Dominant Resistancementioning
confidence: 99%
“…1, Cooley et al, 2000; 2, Ren et al, 2000; 3, Takahashi et al, 2001; 4, Takahashi et al, 2002; 5, Takahashi et al, 2004; 6, Sekine et al, 2006; 7, Chisholm et al, 2000; 8, Whitham et al, 2000; 9, Decroocq et al, 2009; 17, Provvidenti and Hampton, 1992; 18, Ma et al, 2010; 25, Moury and Verdin, 2012; 30, Grube et al, 2000; 31, Tomita et al, 2008; 32, Tomita et al, 2011; 33, Matsumoto et al, 2008; 34, Sawada et al, 2004; 43, De La Cruz et al, 1997; 44, Holmes, 1937; 45, Berzal-Herranz et al, 1995; 50, Anagnostou et al, 2000; 65, Hayes et al, 2004; 66, Hajimorad and Hill, 2001; 67, Hajimorad et al, 2005a; 68, Wen et al, 2013; 69, Eggenberger et al, 2008; 105, Whitham et al, 1994; 106, Erickson et al, 1999; 107, Baker et al, 1995; 108, Dinesh-Kumar et al, 1995; 109, Dinesh-Kumar et al, 2000; 110, Padgett and Beachy, 1993; 111, Padgett et al, 1997; 127, Vallejos et al, 2006; 128, Ariyarathne et al, 1999; 129, Collmer et al, 2000; 130, Kelly et al, 1995; 131, Kyle et al, 1986; 132, Fisher and Kyle, 1994; 133, Fisher and Kyle, 1996; 134, Zhou et al, 2007; 135, Garrido-Ramirez et al, 2000; 136, Seo et al, 2004; 137, Seo et al, 2007; 138, Wang et al, 1999; 139, Gururani et al, 2012; 156, Seo et al, 2006; 158, Yang et al, 2003; 159, Rai, 2006; 160, Harper et al, 2010; 166, Hanson et al, 2000; 167, Verlaan et al, 2013; 169, Ishibashi et al, 2007; 170, Ishibashi et al, 2012; 171, Pelham, 1966; 172, Yamafuji et al, 1991; 173, Meshi et al, 1988; 174, Kato et al, 2013; 179, Finlay, 1953; 180, Holmes, 1948; 181, Brommonschenkel et al, 2000; 182, Hallwass et al, 2014; 183, Hoffmann et al, 2001; 188, Hall, 1980; 189, Meshi et al, 1989…”
Section: Dominant Resistancementioning
confidence: 99%
“…It is already reported that the L gene occur in a cluster of resistance genes located on chromosome 11 in a position that apparently overlaps with resistance gene clusters in tomato and pepper (Grube et al 2000b). Lefebvre (2004) reported the existence of R-gene cluster where disease resistance QTLs for potyvirus, cucumber mosaic virus (CMV), Tomato spotted wilt virus (TSWV), and Phytophthora capsici.…”
Section: Discussionmentioning
confidence: 99%
“…We named these resistance genes 'cmr3E' and 'cmr3L' respectively. Studies for the resistance to CMV in C. annuum have been reported many research groups, most of them were incomplete dominant and quantitatively inherited (Caranta et al, 1997(Caranta et al, , 2002Grube et al, 2000), except for Cmr1 (Kang et al, 2010). Cmr1 on the LG2 is the only dominant resistance gene known in pepper, but resistance is broken down by CMV P1 strain, requiring more robust CMV resistant germplasm (Kang et al, 2010).…”
Section: Inheritance Of Resistance To CMVmentioning
confidence: 99%
“…In some cucurbits, resistance to CMV was controlled by one recessive gene (Kang et al, 2005), tomato and Arabidopsis have single dominant gene for resistance (Stamova and Chetelat, 2000;Takahashi et al, 2001Takahashi et al, , 2002. Several poly-genes for resistance were reported in Capsicum species including 'Perennial' (Caranta et al, 1997;Chaim et al, 2001;Grube et al, 2000;Lapidot et al, 1997), 'Vania' (Caranta et al, 2002), C. baccatum 'PI439381-1-3' (Suzuki et al, 2003) and C. frutescens 'BG2814-6' (Grube et al, 2000). In Arabidopsis and tomato, single dominant gene RCY and Cmr were suggested for resistance (Stamova and Chetelat, 2000;Takahashi et al, 2001Takahashi et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%